Abnormal Returns on Tourism Shares in The Chinese Stock Exchanges Amid The COVID-19 Pandemic - Venus Liew, Khim Sen (Universiti Putra Malaysia (UPM), 2020)
This study finds significant immediate adverse impact of the novel coronavirus (COVID19) pandemic on tourism shares listed in the Shanghai and Shenzhen stock exchanges, in terms of breadth and depth. Overall, prices of these shares plunged by 20% in three consecutive days in response to pandemic fears, before technical rebound set in. Significant negative cumulative abnormal returns after the Wuhan lockdown are identified in 18 out of 21 tourism shares traded in the Chinese stock exchanges. These findings could serve as references for the China Security Regulatory Commission to monitor the market in future pandemic management. Investors are advised to avoid tourism shares the moment there is any suspicious development of virus outbreak in the future. Instead, they could look for opportunity to buy dip after massive market decline at the appropriate timing.